Wave propagation in nonlocal orthotropic micropolar elastic solids - Tung, D.X. (Archives of Mechanics, 2021)
The presented paper is concerned with the propagation of Rayleigh waves in an orthotropic nonlocal micropolar elastic half-space. The main aim of the paper is to derive dispersion equations of Rayleigh wave as well as Stroh formalism for the orthotropic nonlocal micropolar medium. Based on the obtained dispersion equation, the effect of material, nonlocality parameter on the Rayleigh wave propagation is considered through some numerical examples.